The performance and genetic variation of first and second generation tropical alfalfa (Medicago sativa) - Bambang Suwignyo; LUKMANA ARIFIN; NAFIATUL UMAMI; MUHLISIN MUHLISIN; BAMBANG SUHARTANTO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Suwignyo B, Arifin L, Umami N, Muhlisin, Suhartanto B. 2021. The performance and genetic variation of first and second generation tropical alfalfa (Medicago sativa). Biodiversitas 22: 3265-3270. This study aimed to compare the growth performance, nutrient content, seed viability, and genetic variation of first- and second-generation alfalfa (Medicago sativa L.). First and second-generation alfalfa seeds were obtained from the Forage and Pasture Science Laboratory, Department of Animal Nutrition and Feed Science, Faculty of Animal Science, Universitas Gadjah Mada (UGM), Yogyakarta, Indonesia. First generation alfalfa (F1) seeds were obtained from cross breeding of two different parental alfalfa varieties, namely, Canadian and local. The second-generation (F2) seeds were obtained from plants of the first-generation alfalfa (F1). A randomized design experiment was conducted using the two types of alfalfa (first- and second generation). Alfalfa from Canada as female parent was used as the baseline in the genetic masker test. Seeds were planted in a polybag, watered twice a day, and received 12 hours of daylight and 4 hours of artificial light. Plants were then harvested 8 weeks after planting by cutting the plant canopy. Genetic variation was examined using the Inter Simple Sequence Repeat (ISSR) method followed by descriptive analysis. Germination, plant height, dry matter content, organic matter, and crude protein were assessed as variables using a Student’s T-test. Our results showed that germination, plant height, leaf color, and nutrient content (dry matter, organic matter, and crude protein) of the first- and second-generation alfalfa plants were not significantly different. However, the second-generation alfalfa demonstrated better seed viability than the first generation plants, then it can be categorized as a new genotype (tropical alfalfa) based on genetic variation analysis.